Trend Penelitian Project-Based Learning Di Perguruan Tinggi 2014-2023 Melalui Analisis Bibliometrik - Luqman Hakim; M Ansyar Abdillah; Novita Aprilia; Febriana Nurhidayati; Irwan Adimas Ganda Saputra (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2023)
This study aims to analyze and review the development of project-based learning in tertiary institutions from 2014 to 2023. The research data used is research that has been published in Scopus indexed scientific journals. The results of data collection obtained as many as 326 documents. The results of research on the topic of Project-based learning in Higher Education show that the trend in numbers is still fluctuating. In detail, the research trend regarding Project-based learning in Higher Education has increased from 2014-2018, 2018-2019 has decreased, 2019-2021 has decreased, 2021-2022 has experienced an increase, and finally, 2022-2023 has decreased. The top author in the Fernandes, S. domain. In this study the results obtained were 6 clusters that had been visualized through the VOSviewer application. The results of this study are based on an overlay visualization that Project-based learning research in Higher Education in the 2014-2023 period is an interesting topic and research trend. The conclusion of this research is that research with the topic of Project-based learning in Higher Education, which is associated with various variables, and research trends that have been carried out, and the potential for research with the topic of Project-based learning in Higher Education can be carried out.